2020
DOI: 10.1177/1352458520972573
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profile of serum neurofilament light in multiple sclerosis: Implications for patient monitoring

Abstract: Objective: To understand how longitudinal serum neurofilament light chain (sNfL) patterns can inform its use as a prognostic biomarker in multiple sclerosis (MS) and evaluate whether sNfL reflects MS disease activity and disease-modifying therapy usage. Methods: This was a post hoc analysis of longitudinal data and samples from the ADVANCE trial (NCT00906399) of patients with relapsing–remitting MS (RRMS). sNfL was measured every 3 months for 2 years, then every 6 months for 4 years. Regression models explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 34 publications
3
52
3
1
Order By: Relevance
“…Considering the temporal increase of sNfL levels following axonal injury over 3 to 6 months, 35 studies are also required to investigate the optimal frequency of sNfL assessment. 12,18,19 In this respect, more frequent sNfL assessment may further improve identification of patients at higher risk of future disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the temporal increase of sNfL levels following axonal injury over 3 to 6 months, 35 studies are also required to investigate the optimal frequency of sNfL assessment. 12,18,19 In this respect, more frequent sNfL assessment may further improve identification of patients at higher risk of future disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies has established sNfL as marker of disease activity, drug response, and prediction of the disease course, both on clinical and MRI grounds. 9 19 However, the practical value of sNfL as a monitoring tool for clinical practice has been less studied. 13 20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For multiple sclerosis (MS), it has been reported that baseline serum NfL (sNfL) is a predictor of long-term brain atrophy, development of new T2 lesions, T2 lesion volume, gadolinium (Gd+) lesions, and increased likelihood of progression from radiologically isolated syndromes or clinically isolated syndromes to clinically definite MS (10, 11). In addition, sNfL levels are higher and more variable in patients with evidence of active MS and decrease with a DMT (11). Multiple reports have shown that sNfL levels are responsive to treatment with MS DMTs (12-15).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, measurement of a structural axonal protein, neurofilament, in serum or plasma has shown promise as a marker of neuroaxonal injury and a measure of treatment response. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%